Automorphisms of semigroups of k-linked upfamilies - Gavrylkiv, V.M. (Український математичний вісник, 2017)
In the paper, we study automorphisms of the extensions of groups, finite monogenic semigroups and describe the automorphism groups of extensions of null semigroups, almost null semigroups, right zero semigroups and left zero semigroups. The author would like to express his sincere thanks to the anonymous referees for a very careful reading of the paper and for all their insightful comments and valuable suggestions, which improve considerably the presentation of this paper.